2018
DOI: 10.3390/su10082703
|View full text |Cite
|
Sign up to set email alerts
|

Moral Values as Factors for Social Acceptance of Smart Grid Technologies

Abstract: Smart grid technologies are considered an important enabler in the transition to more sustainable energy systems because they support the integration of rising shares of volatile renewable energy sources into electricity networks. To implement them in a large scale, broad acceptance in societies is crucial. However, a growing body of research has revealed societal concerns with these technologies. To achieve sustainable energy systems, such concerns should be taken into account in the development of smart grid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 107 publications
(322 reference statements)
0
26
0
Order By: Relevance
“…Their review found that acceptance of smart grid technology was directly tied to values such as security of supply, transparency, and, above all, environmental sustainability. The smart grid's "contribution to the environmental sustainability of energy systems" was the most often cited driver of acceptance, while barriers included data privacy, data security, (mis)trust, health, justice, and reliability [45] (p. 9). These studies suggest the value of combining seemingly distinct sets of search terms in order to understand how researchers view public engagement with energy transitions.…”
Section: Methodsmentioning
confidence: 99%
“…Their review found that acceptance of smart grid technology was directly tied to values such as security of supply, transparency, and, above all, environmental sustainability. The smart grid's "contribution to the environmental sustainability of energy systems" was the most often cited driver of acceptance, while barriers included data privacy, data security, (mis)trust, health, justice, and reliability [45] (p. 9). These studies suggest the value of combining seemingly distinct sets of search terms in order to understand how researchers view public engagement with energy transitions.…”
Section: Methodsmentioning
confidence: 99%
“…Digitalisation of electricity networkscommonly denominated by the umbrella term 'smart grids'is considered as an important enabler to transition to a more sustainable electricity system, as it allows dealing more effectively and efficiently with intermittent supply from wind and solar energy (Muench, Thuss, and Guenther 2014). The functioning of smart grids depends to a large extent on collection, sharing, and processing of real-time data on electricity use, which raises serious concerns regarding, for example, consumer data privacy and security (Milchram et al 2018b).…”
Section: Digitalising Electricity Networkmentioning
confidence: 99%
“…Recently, scholars have argued that a broader range of moral values beyond privacy-i.e. trust, inclusiveness, and affordability of energy-can influence the social acceptance of smart grid technology (such as smart meters) (Milchram et al 2018). What these and other studies have in common is that they implicitly argue that incorporating social and ethical values (mostly privacy) into smart meters may increase the likelihood of their acceptance.…”
Section: Social Acceptance Ethical Acceptability and Valuesmentioning
confidence: 99%